Comparison of Sharia Governance Between Bank Muamalat and Bank BTN Syariah - Nurita Sari; Mugiyati Mugiyati (Fakultas Studi Islam Universitas Islam Kalimantan Muhammad Arsyad Al Banjary, 2024)
Every business has a management strategy to maintain and develop its business, including Sharia financial institutions. The large potential of the Islamic finance industry has a positive impact on national economic growth, therefore it is important to maintain this stability. Good governance is one of the things that must be paid attention to, as well as the governance of Sharia financial institutions must comply with Sharia principles, to maintain the trust of stakeholders in the Sharia banking and finance industry. Moreover, there are rumors that two large sharia financial institutions will merge . This research aims to compare Sharia governance between Bank Muamalat and BTN Syariah, which have significant differences in background. This research uses qualitative methods with a library study approach, and analyzes and selects relevant library sources. Research result comparison of two Sharia banks that are planned to merge into a larger Sharia bank , although both banks follow Sharia governance principles, they both have different approaches due to different focuses and backgrounds. Bank Muamalat, as a pure sharia bank, has a more comprehensive sharia implementation and structure. Meanwhile, BTN Syariah as a sharia business unit of a conventional bank, focuses more on implementing sharia principles in housing products. Both banks demonstrate a strong commitment to Sharia principles and comply with supervision, the Sharia Supervisory Board (DPS), and applicable laws.